(untitled) - Weltman, Barbara (Hoboken, New Jersey, 2014)
Informative and accessible, J.K. Lasser's guide... is designed for you, the self-employed person working alone as a service provider, to help pin down all of the tax breaks to which you may be entitled. Divided into three comprehensive parts, this reliable resource will help you : [1] Learn the basics of tax reporting: from what it means to be self-employed and an overview of what you have to report - as well as where and when - to becoming familiar with Schedule C. [2] Discover the various types of deductions and credits you can claim to reduce revenue that's taxed. [3] Become familiar with an array of planning strategies that you can use to make better business decisions throughout the years as well as other strategies you can employ as your business grows ... and much more.
Keywords: Thuế thu nhập,Income tax; Luật và các văn bản quy phạm pháp luật,Law and legislation; Hoa Kỳ,United States